(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article describes the rich and varied religious ideas in the life of the peoples of Central Asia, which are reflected in the examples of cultural monuments, and when the religion of Islam penetrated the region, local traditions merged with “Islamic culture” and a new system was created. Representatives of Sufism, who made a great contribution to the development of Islamic science, came from the Tashkent oasis, the architectural monuments and shrines built by them were a place of spirituality for the population in the Middle Ages, these monuments are unique examples of Islamic architecture in the 14-16 centuries, and now these shrines attract local and foreign tourists. Scientific opinions and considerations are put forward that the attraction will make a great contribution to the economy of our country.